Espaços de autonomia e negociação: a atuação dos deputados provinciais paraibanos no cenário político imperial (1855-1875) - Segal, Myrai Araújo (2017)
Based on the analysis of a diversified documentary corpus, which includes the Annals, Minutes and the Internal Regiment of the Provincial Legislative Assembly of Paraíba´s province, Reports of the Presidents of Provinces and newspapers from the 19th century, so, in this study we aimed to understand the performance of the provincial deputies from Paraíba in the Second Reign, specifically between 1855 and 1875, a period in which there was a reconfiguration of national politics. Departing from the presupposition that the Provincial Legislative Assemblies, created by the Additional Act (1834), were constituted as important spaces of power where its members could discuss and legislate about the most varied issues, thus, enjoying considerable autonomy and contributing for the Brazilian national state construction. Based on the concept of Political Cultures and Sociability Networks, we have analyzed the functioning of Provincial Legislative Assembly of Paraíba, ruled by a series of "rituals", and elaborate a prosopographic study of the provincial deputies who acted in the adopted temporal cut, especially those who graduated in Law by the Faculty of Olinda/Recife, where a considerable part obtained the diploma of superior course. Corroborating with the historiography, we identified that this type of formation was configured as one of the national political elite distinctions, since the majority of the provincial deputies that managed to reach the Chamber of Deputies were composed of bachelors in Law, as exemplified by the trajectories of paraiban politicians as Felizardo Toscano de Brito and Father Lindolfo Correia das Neves. In view of the relationship of provincial deputies and other agents of the political elite, such as provincial councilors and presidents, we also discussed municipalities and public instruction in Paraíba, issues which were often at the heart of the debates and that, being constituted as one of the fields of action of the provincial deputies, can be considered relevant spaces of autonomy.